10th Anniversary of Axioms: Mathematical Physics - Haubold, Hans (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue of the journal Axioms collects submissions in which the authors report their perceptions and results in the field of mathematical physics and/or physical mathematics without any preconditions of the specific research topic. The papers are intended to provide the reader with a broad window into the status of the research field showing our understanding of how a known concept changes our thinking in that area of science. The papers in the Special Issue highlight the current two issues in physics and mathematics under hot debate: fractional calculus and entropy.